Ecological and socio-economic factors affecting agricultural intensification in the West African savannas: evidence from Northern Nigeria - Okike, Iheanacho; Jabbar, M.A.; Manyong, Victor M.; Smith, Jimmy W. (Informa UK Limited, 2005)
Agricultural intensification in West Africa is at an early stage and the process is taking place through various pathways. Population pressure and market access are generally considered as major factors driving intensification and crop-livestock interaction. In this paper both ecology and economic factors and their interactions are hypothesized as driving forces in intensification and crop-livestock interaction. Analyses of a survey involving farming households in Nigeria confirm the hypothesis and show that the degree of intensification is higher in the Sudan savanna than the Northern Guinea savanna. Intensification is occurring mostly through higher land and labor use intensity, higher livestock stocking rates and application of more manure per hectare. It is concluded that policies to enhance market access will facilitate the process and that different technological options need to be pursued in the two agroecological zones to facilitate intensification.